Evolution of factors shaping the endoplasmic reticulum - Kontou, Aspasia; Herman, Emily K; Field, Mark C; Dacks, Joel B; Koumandou, V Lila (Traffic, 2022)
Endomembrane system compartments are significant elements in virtually all eukaryotic cells, supporting functions including protein synthesis, post-translational modifications and protein/lipid targeting. In terms of membrane area the endoplasmic reticulum (ER) is the largest intracellular organelle, but the origins of proteins defining the organelle and the nature of lineage-specific modifications remain poorly studied. To understand the evolution of factors mediating ER morphology and function we report a comparative genomics analysis of experimentally characterized ER-associated proteins involved in maintaining ER structure. We find that reticulons, REEPs, atlastins, Ufe1p, Use1p, Dsl1p, TBC1D20, Yip3p and VAPs are highly conserved, suggesting an origin at least as early as the last eukaryotic common ancestor (LECA), although many of these proteins possess additional non-ER functions in modern eukaryotes. Secondary losses are common in individual species and in certain lineages, for example lunapark is missing from the Stramenopiles and the Alveolata. Lineage-specific innovations include protrudin, Caspr1, Arl6IP1, p180, NogoR, kinectin and CLIMP-63, which are restricted to the Opisthokonta. Hence, much of the machinery required to build and maintain the ER predates the LECA, but alternative strategies for the maintenance and elaboration of ER shape and function are present in modern eukaryotes. Moreover, experimental investigations for ER maintenance factors in diverse eukaryotes are expected to uncover novel mechanisms.
Keywords: Eukaryotic Cells; Protein Transport; endoplazmatické retikulum; eukaryotické buňky; transport proteinů; Endoplasmic Reticulum